MARKET ANALYSIS OF SEMISOLID DOSAGE FORMS REGISTERED IN UKRAINE AND RESEARCH OF EXCIPIENTS INCLUDED TO THEIR FORMULAS - Vons, В. V.; Chubka, M. B.; Groshovyi, T. A. (Фармацевтичний часопис, 2015)
it has been investigated the domestic market of semisolid dosage forms registered in Ukraine. Excipients as a part of various semisolid dosage forms have been studied. It has been found that semisolid dosage forms include basic substrate, emulsifiers, gelling agents, solvents, antimicrobial preservatives, antioxidants, solubilizers, colorants, flavors, stabilizers pH and thickeners.